2003 Handbook of Employment Regulations Affecting Florida Farm Employers and Workers: Polygraph Protection for Employees [Federal] - Leo C. Polopolus; Michael T. Olexa; Fritz Roka; Carol Fountain (EDIS)
Polygraph Protection for Employees establishes rights of employees pertaining to polygraph tests. This is EDIS document FE411, a publication of the Department of Food and Resource Economics, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida, Gainesville, FL. Published July 2003. This information is included in Circular 1200, Handbook of Employment Regulations Affecting Florida Farm Employers and Workers.